ITO film stack engineering for low-loss silicon optical modulators - Evgeniy S. Lotkov; Aleksandr S. Baburin; Ilya A. Ryzhikov; Olga S. Sorokina; Anton I. Ivanov; Alexander V. Zverev; Vitaly V. Ryzhkov; Igor V. Bykov; Alexander V. Baryshev; Yuri V. Panfilov; Ilya A. Rodionov (Scientific Reports, 2022)
Abstract The Indium Tin Oxide (ITO) platform is one of the promising solutions for state-of-the-art integrated optical modulators towards low-loss silicon photonics applications. One of the key challenges on this way is to optimize ITO-based thin films stacks for electro-optic modulators with both high extinction ratio and low insertion loss. In this paper we demonstrate the e-beam evaporation technology of 20 nm-thick ITO films with low extinction coefficient of 0.14 (Nc = 3.7·1020 cm−3) at 1550 nm wavelength and wide range of carrier concentrations (from 1 to 10 × 1020 cm−3). We investigate ITO films with amorphous, heterogeneously crystalline, homogeneously crystalline with hidden coarse grains and pronounced coarsely crystalline structure to achieve the desired optical and electrical parameters. Here we report the mechanism of oxygen migration in ITO film crystallization based on observed morphological features under low-energy growth conditions. Finally, we experimentally compare the current–voltage and optical characteristics of three electro-optic active elements based on ITO film stacks and reach strong ITO dielectric permittivity variation induced by charge accumulation/depletion (Δn = 0.199, Δk = 0.240 at λ = 1550 nm under ± 16 V). Our simulations and experimental results demonstrate the unique potential to create integrated GHz-range electro-optical modulators with sub-dB losses.